2016
DOI: 10.1371/journal.pntd.0004781
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Surveillance Identifies Multiple Transmissions of Typhoid in West Africa

Abstract: BackgroundThe burden of typhoid in sub-Saharan African (SSA) countries has been difficult to estimate, in part, due to suboptimal laboratory diagnostics. However, surveillance blood cultures at two sites in Nigeria have identified typhoid associated with Salmonella enterica serovar Typhi (S. Typhi) as an important cause of bacteremia in children.MethodsA total of 128 S. Typhi isolates from these studies in Nigeria were whole-genome sequenced, and the resulting data was used to place these Nigerian isolates int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 31 publications
2
54
0
Order By: Relevance
“…Salmonella Typhi H58 is a highly clonal multidrug-resistant haplotype of Salmonella Typhi that is being reported with increasing frequency from many countries in Africa and Asia. 42 , 43 Continual antimicrobial resistance monitoring has become an essential adjunct to assessing how best to control typhoid fever. 44 Molecular analyses, including PFGE and more recently WGS have confirmed that South Africa remains highly vulnerable to the introduction of multidrug-resistant typhoid fever and potential outbreaks that may result from this, 31 , 32 particularly as ongoing outbreaks of fluoroquinolone-resistant typhoid fever are reported from neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella Typhi H58 is a highly clonal multidrug-resistant haplotype of Salmonella Typhi that is being reported with increasing frequency from many countries in Africa and Asia. 42 , 43 Continual antimicrobial resistance monitoring has become an essential adjunct to assessing how best to control typhoid fever. 44 Molecular analyses, including PFGE and more recently WGS have confirmed that South Africa remains highly vulnerable to the introduction of multidrug-resistant typhoid fever and potential outbreaks that may result from this, 31 , 32 particularly as ongoing outbreaks of fluoroquinolone-resistant typhoid fever are reported from neighboring countries.…”
Section: Discussionmentioning
confidence: 99%
“…Typhi population. Importantly, while genomic epidemiology has been applied to study typhoid transmission, antimicrobial resistance evolution and antibiotic treatment failure in various settings [6668], this study provides an important proof-of-principle demonstration that this approach can also provide useful insights into the impact of typhoid vaccines on circulating bacterial populations. This should motivate the adoption of WGS methods to monitor S .…”
Section: Discussionmentioning
confidence: 99%
“…H58 S . Typhi disease is moving through areas of East and Southern Africa, while, non-H58 haplotypes are implicated in the Western and Northern regions, illustrating the heterogeneous nature of the disease on the continent[ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%